Bioethics education in the science curriculum : evaluation of strategies for effective and meaningful implementation. - Dawson, Vaille (Curtin University, 1999)
Although science is viewed by some as objective, analytical and unaffected by morals and values, the practice of science does raise many ethical issues. From an ethical standpoint, science teachers have an obligation to ensure that their students develop the skills to enable them to evaluate and make decisions about ethical issues associated with scientific advances so that they can make informed choices as adults. An appropriate forum for such a pedagogical concern is the subject of bioethics education.The purpose of this doctoral study was to investigate the teaching of bioethics in science. Specifically, the study attempted to evaluate the effectiveness of a range of innovative pedagogical strategies utilised by teachers who were incorporating bioethics education into their secondary science curricula. Bioethics education is concerned with enabling students, firstly, to appreciate the range of ethical issues associated with the life sciences and, secondly, to develop decision making skills based on ethical theories.Using an interpretive case study approach underpinned by a constructivist theoretical framework, I examined the teaching practice of three science teachers in different school systems. Each of these teachers taught Year 10 or Year 11 science courses that included a bioethics component. The research process was informed by an ethic of care and the constructivist criteria of credibility, transferability and ontological authenticity.As a result of the early data generated, I adopted the role of a bricoleur and used alternative research methods to pursue emergent research questions. I developed a survey consisting of four bioethical dilemmas. Bioethics students were asked to resolve each of the dilemmas and provide reasons to support their decisions. Using an ex post facto research design, I compared students who had studied bioethics with a comparison group of students who had not. I also wrote narrative tales in an endeavour to provide an authentic account of the learning of individual students. Commentaries on the tales, by students and teachers, helped to enrich my understanding of students' learning experiences in the bioethics classes.The research findings are presented as 'inferences', a term which acknowledges the context dependent nature of the data generated. Five themes emerged from the data analysis which, together, indicate (1) the nature of potentially successful teaching strategies for bioethics education and (2) obstacles to students' successful engagement in learning bioethics: teacher attributes; design of bioethics courses; student attributes; impact on student learning; and physical and social constraints. Another key finding concerns the difficulty facing researchers who wish to 'measure' the impact of bioethics teaching on student learning.All three teachers displayed potentially successful teaching strategies. They were committed to the inclusion of bioethics education in their science courses. They had clearly articulated pedagogical goals related to bioethics education. They endeavoured to create safe learning environments in which students could clarify and explore their developing ethical values. When students expressed extreme views, the teachers, through careful questioning, challenged them to consider alternative ethical positions.In relation to the design of bioethics education courses, most of the learning activities in which students participated were based on small group and whole-class discussion (e.g., role plays, oral presentations). These activities provided opportunities for students to examine a topic in depth. Importantly, students were provided with information to help them understand the scientific content area before they could appreciate the associated ethical issues.In the three cases, it appears that bioethics education had a variable effect on student learning. Attributes were identified that may have influenced student engagement in opportunities to learn bioethics: the students' moral maturity, academic ability, attitude to learning, beliefs about science and ethics, family and religious background.Evidence suggests that exposure to bioethics education can affect favourably students' attitudes to science. However, the results of the bioethical dilemma survey suggest that, on average, there was no difference in the way that students resolved dilemmas, regardless of whether or not they had been exposed to bioethics education. Although there was considerable variation amongst students, most of the students' responses differed from those of experts in that the students tended to focus solely on the rights of individuals, without considering the long term consequences of their decisions.Constraints were identified that may adversely affect the impact of bioethics education in science: scarcity of resources, including insufficient teaching time; and, amongst science teachers, lack of expertise in the content areas that raise bioethical issues and lack of experience in the types of learning activities appropriate for bioethics education.The findings of this research study are significant as they highlight important issues that may need to be considered by curriculum planners and science teachers who wish to incorporate bioethics education into science curricula.